2004
DOI: 10.1590/s0074-02762004000800005
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus detection by using reverse transcription-polymerase chain reaction in saliva and progeny of experimentally infected Aedes albopictus from Brazil

Abstract: Oral susceptibility and vertical transmission of dengue virus type 2 (DENV-2) in an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 30 publications
2
34
0
8
Order By: Relevance
“…albopictus is considered a potential vector of dengue in Brazil (Castro et al 2004). If this is confirmed, the observed trend towards larger females during the dengue season (summer) may contribute to a higher level of transmission since larger mosquitoes are more fecund (Naksathit & Scott 1998) and are apparently better vectors in terms of their physiologic capability to acquire dengue infection orally (Sumanochitrapon et al 1998).…”
mentioning
confidence: 94%
“…albopictus is considered a potential vector of dengue in Brazil (Castro et al 2004). If this is confirmed, the observed trend towards larger females during the dengue season (summer) may contribute to a higher level of transmission since larger mosquitoes are more fecund (Naksathit & Scott 1998) and are apparently better vectors in terms of their physiologic capability to acquire dengue infection orally (Sumanochitrapon et al 1998).…”
mentioning
confidence: 94%
“…Vertical transmission is of great epidemiological importance and suggests that vector mosquitoes may play an important role in the maintenance (Castro et al 2004) of virus in the environment and mosquitoes may act as reservoirs of these viruses (Joshi et al 2006). Laboratory data demonstrated that the mosquito Aedes aegypti may be infected with double combinations of different arboviruses and that it is also capable of transmitting these viruses simultaneously.…”
mentioning
confidence: 99%
“…The infected A.aegypti females may also transmit the virus to the next generation of mosquitoes by transovarial. Although very seldom, this means of transmission is of great epidemiological significance demonstrating that the vector play an important role in the persistence of the virus in the environment and act as reservoirs (WORLD HEALTH ORGANIZATION, 2001;Castro et al, 2004;Joshi et al, 2006). Human beings are the main host and the virus replicates in the blood stream.…”
Section: Transmissionmentioning
confidence: 99%